Measurement and Prediction of Densities of Ternary Aqueous Mixtures Involving Sodium Polyacrylate - Z A Noor Fadzlina; T T Teng; M Abdul Rahman (ASEAN Journal of Chemical Engineering, 2004)
The densities of the binary aqueous solutions of sodium polyacrylate (NaPM) at 20°C, 25°C, and 300oC up to 0.17 m and LiCI at 25°C and 300C up to 3.13 m were measured using a vibrating tube digital densitimeter. The measured experimental data were then fitted to the polynomial d = do + IA;m'. The densities of the ternary aqueous systems NaPM-NaCI, NaPM-LiCI, and NaPM-sucrose were also =1 measured from 20°C to 30°C. The isopycnotic equation, Imi / moi was used to predict the densities of the ternary aqueous systems mentioned. The results show that predicted and observed density values are in good agreement. The overall percentage error of density prediction for the system NaPM-NaCI-H20 is 0.067. For the system NaPM-LiCI-HP,the overall percentage error is 0.074; and, for the system NaPM-sucrose-H20, the overall percentage error is 0.065.